Polarization features of acoustic spectra in uniaxial and biaxial nematic liquid crystals - Kovalevsky, M.Y.; Logvinova, L.V.; Matskevych, V.T. (Вопросы атомной науки и техники, 2012)
The results of investigation of uniaxial and biaxial nematic liquid crystals dynamics with molecules of the various forms are presented. These condensed matters possess internal spatial anisotropy and for their adequate description introduction of additional dynamic quantities is necessary. They are vectors of spatial anisotropy and conformational degrees of freedom. Investigation of dynamics of the given condensed matters is based on Hamiltonian formalism in which framework the nonlinear dynamic equations for uniaxial and biaxial nematic liquid crystals are derived. Spectra of collective excitations are obtained and their polarization features are investigated.